Letter from my Father. - Black, Dasia (Brandl & Schlesinger, 2012)
Ester was a four-year-old child during the Holocaust in Poland when she was told that both her parents had been killed. In 'Letter from my Father' Dasia Black (born Ester Hadasa) tells of her struggle as a child to survive the loss of her family, her name and identity.